Verrucous Carcinoma of the Esophagus Eluding Multiple Sets of Endoscopic Biopsies and Endoscopic Ultrasound: A Case Report and Review of the Literarure. (1st July 2004) - Devlin, Shane; Falck, Vincent; Urbanski, Stefan J; Mitchell, Philip; Romagnuolo, Joseph
Abstract : A 56-year-old woman was noted to have a 5 cm to 6 cm long, irregular narrowing of the distal esophagus on an upper gastrointestinal series. Initial endoscopy revealed a polypoid mass in the distal esophagus and concurrent endoscopic ultrasound revealed changes typical of inflammation but no evidence of an obvious neoplastic process. Repeated biopsies revealed only inflammation with no evidence of malignancy. Only after prolonged acid suppression did biopsies reveal verrucous carcinoma of the esophagus. The patient underwent a trans-hiatal esophagectomy and has remained well with no evidence of progression since. Verrucous carcinoma is a rare variant of squamous cell carcinoma, taking on a papillary or warty appearance grossly. Histological diagnosis may be difficult because this tumour typically shows no high-grade dysplasia. Therefore, diagnosis can be challenging, often requiring multiple sets of endoscopic biopsies due to the overlying hyperkeratotic layer. Of the 20 cases that have been reported, this is the second to provide an endosonographic description and the first to describe a change in endoscopic appearance with acid suppression.